Model Budidaya Kepiting Soka Skala Rumah Tangga Sistem Apartemen Sebagai Sarana Edukasi Masyarakat Pulau Bangka - Ardiansyah Kurniawan; Muhammad Haikal; Nur Rahmadina; Sonia Berliani (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Mangrove crab is one of the important and potential economic commodities on Bangka Island. One of the products is soka crab. Opportunities and prospects for soft crab cultivation have led to the emergence of aquaculture ponds. Cultivation of this horizontal system requires high costs and is less applicable for household scale. Bangka Belitung University students build a fish farming business unit with a vertical apartment system. The apartment uses plastic boxes arranged vertically equipped with water re-circulation. The duration of crabs reached molting at 27 -30 days rearing with 100% survival. In addition to being a student entrepreneurship lesson, this business unit is an educational model for the people of Bangka Island. The local government also sent envoys to study the production of this soft crab. This business provides opportunities for new entrepreneurs from the academic community on campus, becomes the choice of the local government to move the regional economy, as well as an option for the people of Bangka who are trying to escape from dependence on tin mining